Parafoveal X-masks interfere with foveal word recognition: evidence from fixation-related brain potentials - Hutzler, Florian; Fuchs, Isabella; Gagl, Benjamin; Schuster, Sarah; Richlan, Fabio; Braun, Mario; Hawelka, Stefan (Frontiers in Systems Neuroscience, 2013)
Abstract The boundary paradigm, in combination with parafoveal masks, is the main technique for studying parafoveal preprocessing during reading. The rationale is that the masks (e.g., strings of X’s) prevent parafoveal preprocessing, but do not interfere with foveal processing. A recent study, however, raised doubts about the neutrality of parafoveal masks. In the present study, we explored this issue by means of fixation-related brain potentials (FRPs). Two FRP conditions presented rows of 5 words. The task of the participant was to judge whether the final word of a list was a “new” word, or whether it was a repeated (i.e., “old”) word. The critical manipulation was that the final word was X-masked during parafoveal preview in one condition, whereas another condition presented a valid preview of the word. In two additional event-related brain potential (ERP) conditions, the words were presented serially with no parafoveal preview available; in one of the conditions with a fixed timing, in the other word presentation was self-paced by the participants. Expectedly, the valid-preview FRP condition elicited the shortest processing times. Processing times did not differ between the two ERP conditions indicating that “cognitive readiness” during self-paced processing can be ruled out as an alternative explanation for differences in processing times between the ERP and the FRP conditions. The longest processing times were found in the X-mask FRP condition indicating that parafoveal X-masks interfere with foveal word recognition.